Wind, Water, and Risk: Shaping a Transnational History of the Western North Pacific. Issue 1 (9th December 2015) - Bankoff, Greg
Abstract: The peoples who inhabit the states that lie in the direct paths of typhoons in the Western North Pacific share a common history of repeated dislocation, destruction, and death that delimits a zone of comparative enquiry and historiographical interest. The track left by typhoons across ocean and land perfectly outline the dimensions of a more transnational historical region encompassing the Philippines, Vietnam, China, Korea, Japan, Taiwan, and the island states of Micronesia. The peoples of these lands are bound together by a common experience of risk. Wind and water together offer a radical alternative historiography to state-centred master narratives that are revealed by pursuing issues and questions that transcend the spatial and temporal boundaries of any one state or region.